Urgensi Peralihan Pembinaan Pengadilan Pajak di Bawah Mahkamah Agung - I Gede Yudi Arsawan; Emil Maula (International Forum of Researchers and Lecturers, 2023)
Abstract. Tax is one of the state's incomes that has a large contribution to state finances compared to other state income. In the implementation of tax collection, it is not uncommon for there to be various kinds of disputes between the tax authorities and the public who are taxpayers, which are called tax disputes. Tax dispute resolution is resolved through a judicial institution called the Tax Court. However, currently the authority for guidance over the Tax Court is still carried out by the Ministry of Finance and the Supreme Court, even though the Tax Court is part of the judicial institution. This research uses a type of juridical-normative research which focuses on the use of secondary data. This type of research is a procedure for finding the truth based on the logic of legal science from a normative point of view. The results of this research found that after the Constitutional Court Decision Number 26/PUU-XXI/2023, the full authority to guide the Tax Court had to be transferred to the Supreme Court. It is recommended that the implementation of the transfer of guidance authority be carried out in stages as soon as possible in order to provide legal certainty regarding the long-standing overlap of authority between the executive and judicial powers towards the Tax Court which should be purely part of the judiciary. Keywords: government power, guidance, tax court Abstrak. Pajak merupakan salah satu income negara yang memiliki sumbangan besar terhadap keuangan negara dibandingkan dengan pendapatan negara lainnya. Dalam pelaksanaan penagihan pajak, tidak jarang terdapat berbagai macam perselisihan antara fiskus dengan masyarakat yang merupakan wajib pajak yang disebut dengan sengketa pajak. Penyelesaian sengketa pajak diselesaikan melalui sebuah institusi peradilan yang disebut Pengadilan Pajak. Namun saat ini kewenangan pembinaan atas Pengadilan Pajak masih dilakukan oleh Kementerian Keuangan dan Mahkamah Agung, padahal Pengadilan Pajak merupakan bagian dari lembaga yudikatif. Penelitian ini menggunakan jenis penelitian yuridis-normatif yang menitikberatkan pada penggunaan data sekunder. Penelitian jenis ini adalah prosedur untuk menemukan kebenaran yang didasarkan pada logika keilmuan hukum dari sudut pandang normatif. Hasil penelitian ini menemukan bahwa pasca Putusan MK Nomor 26/PUU-XXI/2023, maka kewenangan pembinaan Pengadilan Pajak sepenuhnya harus dialihkan ke Mahkamah Agung. Disarankan agar pelaksanaan peralihan kewenangan pembinaan tersebut dilaksanakan secara bertahap sesegera mungkin demi memberikan kepastian hukum terhadap tumpang tindih kewenangan yang sudah lama sekali terjadi antara kekuasaan eksekutif dan yudikatif terhadap Pengadilan Pajak yang seharusnya murni sebagai bagian dari yudikatif. Kata kunci: kekuasaan pemerintahan, pembinaan, pengadilan pajak